Enlab 2022
DOI: 10.54227/elab.20220005
|View full text |Cite
|
Sign up to set email alerts
|

Interface Engineering-Inspired Electron Regulation in Pt/Pd Hetero-Metallene for Methanol-Assisted Hydrogen Evolution

Abstract: The small molecule oxidation reaction instead of oxygen evolution reaction coupled with hydrogen evolution reaction can greatly reduce the reaction overpotential of electrochemical water splitting, which is a very efficient and energy-saving hydrogen evolution strategy. Herein, we report an interface engineering constructed two-dimensional ultrathin curled Pt/Pd hetero-metallene for efficient electrocatalytic hydrogen evolution assisted by methanol. The thin-sheet structure of Pt/Pd hetero-metallene provides a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…The design of the reactor and the operating conditions can also influence the catalytic performance of the supported catalyst. [92][93][94] Optimizing parameters such as temperature, pressure, gas flow rate, and residence time can improve the conversion and selectivity of VOC oxidation.…”
Section: Reaction Engineeringmentioning
confidence: 99%
“…The design of the reactor and the operating conditions can also influence the catalytic performance of the supported catalyst. [92][93][94] Optimizing parameters such as temperature, pressure, gas flow rate, and residence time can improve the conversion and selectivity of VOC oxidation.…”
Section: Reaction Engineeringmentioning
confidence: 99%
“…[48][49][50][51] In recent years, modifying the electronic structure of Pd has paved another pathway for substantially enhancing their electrocatalytic performance. [52][53][54][55][56][57][58][59][60] Incorporating H atoms into Pd lattice can tailor the d-band center of Pd and accelerate the reaction kinetics by weakening the bond between the catalyst and reaction intermediate. 61,62 Kabiraz and coworkers have demonstrated that β-PdH cubes and octahedra could deliver enhanced catalytic activity and stability for MOR, due to the ligand effect originating from the interstitial alloying of β-PdH.…”
Section: Electrocatalytic Alcohol Oxidation Reactionmentioning
confidence: 99%
“…In addition, the engineering of nanoparticles on a 2D structure is also an attractive strategy. Nanoparticle (NP)-deposited 2D nanomaterials can amplify the interface effect and improve atomic utilization. More importantly, strong electron interaction at the heterostructure interface can promote the redistribution of electron charge density, adjust the adsorption of intermediates, and reduce the reaction energy barrier. Therefore, the development of Pt/Rh heterostructured metallene is expected to be promising for H 2 production and the selective oxidation of ethylene glycol.…”
Section: Introductionmentioning
confidence: 99%